PELATIHAN PUBLIC RELATION UNTUK MEMBANGUN CITRA POSITIF SEKOLAH - Bradley Setiyadi; Ali Idrus; Firman Firman; Musyaiyadah Musyaiyadah (Universitas Majalengka, 2022)
The existence of Public Relations in an educational institution is as a bridge or mediation between the school and the public so that each element in the school needs to design its relationship with various elements of society in order to achieve a harmonious and harmonious relationship. The relationship between schools and the public, through Public Relations activities, can be interpreted as a means of communication that provides information about schools to the community. Good communication can be felt not only by parents of students, but also the outside community so that it can influence the public to make it a favorite school. Implementing a good Public Relations strategy is one of the important elements to achieve this success. Taking into account the things above, the Public Relations Training for School Managers is very important to provide understanding and improve the skills of school managers, be it principals, vice principals, public relations departments and also teachers, in the field of Public Relations. so that it can help schools in building a positive image to the community. The end result of this service is that schools can design Public Relations activities so that they can be useful for policy makers in schools to build a positive image of the school and improve the quality of education.